Efficacy of hyperthermic intraperitoneal chemotherapy and interval debulking surgery in women with advanced uterine serous carcinoma - Laura M. Chambers; Danielle Chau; Meng Yao; Anthony B. Costales; Peter G. Rose; Chad M. Michener; Robert Debernardo; Roberto Vargas (Elsevier, 2021)
Objective(s): To investigate the efficacy and safety of hyperthermic intraperitoneal chemotherapy (HIPEC) at the time of iterval debulking surgery (IDS) in women with advanced uterine serous carcinoma (USC) following neoadjuvant chemotherapy (NACT). Methods: An IRB-approved single-institution prospective registry was queried to identify women with incidentally identified USC at the time of IDS + HIPEC for high-grade serous carcinoma. Patient demographic, oncologic, and surgical outcomes data were recorded. Univariate analysis determined progression-free survival (PFS) and overall survival (OS). Results: In total, seven patients were found to have advanced USC after undergoing IDS + HIPEC, with a median age of 64.5 years. The majority had stage IV, (n = 6, 85.7%), MMR proficient (n = 5, 71.4%), p53 mutant (n = 6, 85.1%) USC. The median pre-operative CA125 was 24.0U/mL. HIPEC regimen was cisplatin (n = 3, 42.9%) or cisplatin with paclitaxel (n = 4, 57.1%). All patients underwent optimal cytoreduction, with 71.4% (n = 5) having no gross residual disease. Accordion post-operative complications were mild in 14.3% (n = 1), moderate in 57.1% (n = 4) and severe in 14.3% (n = 1); 14.3% (n = 1) had no complications. The median length of stay was 6.5 days (IQR 4-8 days) with a median time to chemotherapy of 33.0 days. The median PFS was 14.0 months (95% CI 3.5-20.8 months), and the median OS was 27.0 months (95% CI 5.1- not reached). Conclusions: In this small, prospective series, we demonstrate that IDS + HIPEC is well tolerated in patients with USC and is associated with favorable PFS and OS following NACT. Further prospective investigation is needed to validate these promising findings in larger, heterogeneous cohorts of women with advanced USC who are not candidates for primary surgical management.